Sleep Deprivation and Its Associated Factors Among Undergraduate Students in Malaysia. (July 2021) - Naito, Rika; Yun Low, Wah; Wan Yuen, Choo
This cross-sectional study examines the prevalence of sleep deprivation and its associated factors among 1017 undergraduate students in Malaysia. Sociodemographic and lifestyle factors such as smoking, alcohol, dietary habits, Internet/smartphone use, physical activity, and sedentary behavior were assessed. Sleep deprivation was defined as sleeping less than 7 hours in a day. There were almost equal proportions of females (51.0%) and males (49.0%), and the average age was 20.71 ± 1.47 years. Prevalence of sleep deprivation was 58.1% and its associated factors were students in Year 3 and Year 4, Chinese ethnicity, Indian ethnicity, and consuming fast food more than once a week. Understanding the associated lifestyle factors with sleep deprivation among young generation will be beneficial to develop public health policies and programs to tackle the issue.